The impact of Woods' model on the development of visual thinking among fifth preparatory students - Taha Bunyan Sultan; Sadiq Ali Bunyan (Zanco Journal of Humanity Sciences)
The research aims to identify the effect of the Woods’ model in developing visual thinking for Fifth preparatory students, and to achieve the goal of the research, the researcher followed the procedures of the experimental approach, as the researchers prepared educational plans according to the Woods model, after the researcher confirmed their validity by presenting them to a group of experts and arbitrators, prepared The two researchers used a test for visual thinking, after confirming its sincerity and reliability, the two researchers used the following statistical methods: (T-test for Two separate samples, Pearson correlation coefficient, and Alpha Cronbach's laboratory equation), and after analyzing the results statistically, the researchers reached the effectiveness of the Woods model in developing visual thinking, and through the results reached by the researcher, a number of recommendations and proposals were presented.